2022
DOI: 10.1007/s10668-022-02793-7
|View full text |Cite
|
Sign up to set email alerts
|

Blood plasma supply chain planning to respond COVID-19 pandemic: a case study

Abstract: The COVID-19 pandemic causes a severe threat to human lives worldwide. Convalescent plasma as supportive care for COVID-19 is critical in reducing the death rate and staying in hospitals. Designing an efficient supply chain network capable of managing convalescent plasma in this situation seems necessary. Although many researchers investigated supply chains of blood products, no research was conducted on the planning of convalescent plasma in the supply chain framework with specific features of COVID-19. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 85 publications
(100 reference statements)
0
0
0
Order By: Relevance
“…They considered the possibility of helicopter usage to transport blood and injured people. Fallahi, Mousavian Anaraki (37) developed a new model for supply chain planning of regular and convalescent plasma during the COVID-19 pandemic. The authors suggested using motivational programs and a transshipment strategy to increase the efficiency of the supply chain .…”
Section: Related Studiesmentioning
confidence: 99%
“…They considered the possibility of helicopter usage to transport blood and injured people. Fallahi, Mousavian Anaraki (37) developed a new model for supply chain planning of regular and convalescent plasma during the COVID-19 pandemic. The authors suggested using motivational programs and a transshipment strategy to increase the efficiency of the supply chain .…”
Section: Related Studiesmentioning
confidence: 99%